Modified nano silicon dioxide blocking agent, preparation method thereof and water-based drilling fluid
By using modified nanosilicon dioxide sealant, the problem of well wall instability caused by drilling fluid ineffectively sealing mud shale nano-scale fractures is solved, and effective sealing of nano-fractures and improving the stability of the well wall is achieved.
Patent Information
- Application Number
- CN202311770577.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-21
- Publication Date
- 2025-06-24
AI Technical Summary
The sealant in existing drilling fluid cannot effectively block nano-scale cracks in mud shale, resulting in serious problems instability of the well wall.
A modified nanosilica sealing agent is used, which consists of nanosilica, amino-containing silane coupling agent, acrylic acid and benzene ring-containing amine substances, and is prepared by ultrasonic dispersion and reaction treatment technology, with a particle size distribution between 35-250 nm.
Modified nanosilicon dioxide sealing agent can effectively seal nano-scale cracks in mud shale formations, stabilize the well walls, improve the rheology, stability and sealing properties of drilling fluids, and reduce the loss of high-temperature and high-pressure filtration.
Smart Images

Figure CN120192758A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oil and gas field drilling, and specifically relates to a modified nano-silica plugging agent, a preparation method thereof, and an aqueous drilling fluid. Background Art
[0002] The problem of wellbore instability is a worldwide technical problem that has not been well solved in the drilling industry. With the complexity and diversity of exploration and development, problems such as hole shrinkage, collapse, lost circulation, and stuck pipe are particularly prominent, seriously affecting the drilling speed, wellbore quality, etc., and restricting the safe and efficient development of oil and gas resources in China. Solving the problem of wellbore stability has important practical significance in protecting oil and gas reservoirs, increasing production, and reducing drilling costs.
[0003] Currently, the particle sizes of commonly used plugging agents in drilling fluids are mostly in the micron level, and they can effectively plug micron-level microfractures. However, the pore sizes of microfractures in shale are extremely small. Therefore, there are high requirements for the particle size of the plugging agent material in the drilling fluid.
[0004] Traditional plugging agents are not easily extruded and deformed, and it is difficult to enter shale microfractures. It is urgent to select nano materials for plugging. Nano materials have the advantages of small particle size, easy deformation, adjustable size, large surface area, etc. Adding them to the drilling fluid can effectively plug shale microfractures and prevent water from entering the shale, and relieve the problem of wellbore instability from external reasons. Therefore, it has important practical significance to prepare a nano-shale plugging agent with good compatibility with aqueous drilling fluids. Summary of the Invention
[0005] Aiming at the problem of wellbore instability caused by the inability of conventional plugging agents to effectively plug nano-fractures in shale, the present invention provides a modified nano-silica plugging agent, a preparation method thereof, and an aqueous drilling fluid. The nano-silica plugging agent can effectively plug nano-level fractures in shale formations, thereby achieving the purpose of stabilizing the wellbore, and can be used to prepare an aqueous drilling fluid, which can effectively solve problems such as wellbore stability and reservoir pollution.
[0006] The present invention is realized through the following technical solutions:
[0007] In a first aspect, the present application provides a modified nano-silica plugging agent, which includes nano-silica, an amino-containing silane coupling agent, acrylic acid, and an amine substance containing a benzene ring.
[0008] Further, the amino-containing silane coupling agent includes γ-methacryloxypropyltrimethoxysilane or γ-aminopropyltriethoxysilane.
[0009] Further, the amine substance containing a benzene ring includes o-toluidine or N-methylaniline.
[0010] Further, the sheet diameter of the nano-silica is 10 nm to 20 nm.
[0011] In a second aspect, the present application provides a method for preparing a modified nano-silica plugging agent, comprising the following steps:
[0012] Modification of nano-silica: The dried nano-silica is added to a dispersion liquid for ultrasonic dispersion, and a silane coupling agent containing an amino group is added dropwise while stirring. After the reaction, it is washed and dried to obtain modified nano-silica.
[0013] The modified nano-silica and toluene are added to a reaction vessel. After ultrasonic dispersion, acrylic acid and an aromatic amine substance are added, and stirred until dissolved. Nitrogen is introduced, and the temperature of the reaction system is raised. After the reaction is completed, it is washed and dried to obtain the modified nano-silica plugging agent.
[0014] Further, the molar ratio among the modified nano-silica, acrylic acid, and the aromatic amine substance is (0.05 - 0.05):(0.02 - 0.03):(0.01 - 0.02).
[0015] Further, the temperature-raising mode of the reaction system is: first raise the temperature to 45°C - 50°C, stir and react for 14 h - 16 h, then raise the temperature to 80°C - 90°C, and continue to react for 2 h - 3 h.
[0016] In a third aspect, the present application provides an aqueous drilling fluid, comprising the above-mentioned modified nano-silica plugging agent or the modified nano-silica plugging agent prepared by the above-mentioned preparation method.
[0017] Further, it further comprises water, bentonite, sodium hydroxide, potassium polyacrylamide coating agent, polyanionic cellulose, humic acid propanesulfonamide copolymer, sulfonated phenolic resin filtration reducer, amidoamine anti-collapse agent, anti-sticking filtration reducer, anti-sticking lubricant, emulsifier, desulfurizer, calcium oxide alkalinity regulator, and nano-barite weighting agent.
[0018] Further, based on 100 parts by weight of water, the addition amount of the bentonite is 2 - 4 parts, the addition amount of the sodium hydroxide is 0.1 - 0.3 parts, the addition amount of the potassium polyacrylamide coating agent is 0.01 - 0.03 parts, the addition amount of the polyanionic cellulose is 0.3 - 0.8 parts, the addition amount of the humic acid propanesulfonamide copolymer is 4 - 6 parts, the addition amount of the sulfonated phenolic resin filtrate reducer is 5 - 6 parts, the addition amount of the amidoamine anti-collapse agent is 3 - 5 parts, the addition amount of the anti-sticking filtrate reducer is 1 - 2 parts, the addition amount of the anti-sticking lubricant is 4 - 5 parts, the addition amount of the emulsifier is 0.3 - 0.5 parts, the addition amount of the modified nano-silica plugging agent is 1 - 5 parts, the addition amount of the desulfurizer is 1 - 1.5 parts, the addition amount of the calcium oxide alkalinity regulator is 0.3 - 0.5 parts, and the addition amount of the nano-barite weighting agent is 0 - 20 parts.
[0019] The preparation method of the water-based drilling fluid is as follows:
[0020] Step 1: Prepare pre-hydrated bentonite slurry. Add bentonite to tap water at a temperature of 70°C, stir evenly at room temperature, then add sodium hydroxide, stir well, and seal and let it stand for hydration.
[0021] Step 2: Configure the drilling fluid. Sequentially add the potassium polyacrylamide coating agent, polyanionic cellulose, humic acid propanesulfonamide copolymer, sulfonated phenolic resin filtrate reducer, amido anti-collapse agent, anti-sticking filtrate reducer, anti-sticking lubricant, emulsifier, desulfurizer, calcium oxide alkalinity regulator, and nano-barite to the pre-hydrated bentonite slurry. Each time a substance is added, it needs to be stirred for 10 - 15 minutes.
[0022] Step 3: After stirring evenly, add the modified nano-silica plugging agent to the bentonite slurry to prepare a drilling fluid containing the high-temperature-resistant modified nano-silica plugging agent.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] (1) The particle size distribution of the novel high-temperature-resistant modified nano-silica plugging agent prepared by the present invention is between 35 - 250 nm, which can effectively plug the nano-scale cracks in the shale formation, thereby achieving the effect of stabilizing the wellbore.
[0025] (2) The water-based drilling fluid prepared by the present invention has good performance in terms of rheology, stability, and plugging property under shale formation conditions. Description of the Drawings
[0026] To more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the accompanying drawings required for the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, without creative efforts, other related drawings can also be obtained based on these drawings. In the drawings:
[0027] Figure 1 It is the particle size distribution diagram of the high-temperature resistant modified nano-silica plugging agent in Embodiment 1 of the present invention;
[0028] Figure 2 It is the particle size distribution diagram of the high-temperature resistant modified nano-silica plugging agent in Embodiment 2 of the present invention. Detailed implementation manners
[0029] To make the objectives, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention.
[0030] Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed present invention, but merely represents the selected embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.
[0031] Embodiment 1
[0032] This embodiment provides a preparation method of a modified nano-silica plugging agent. The specific steps are as follows:
[0033] S1: Place nano-silica with a sheet diameter of 10 nm in a vacuum drying oven at 70 °C for 10 hours. Accurately weigh 2 g of the dried nano-silica, add it to a 40 ml ethanol / water dispersion liquid, ultrasonically disperse for 40 minutes, then dropwise add 2 g of γ-aminopropyltriethoxysilane while stirring, react at a temperature of 70 °C for 8 hours, wash with ethanol, wash repeatedly 3 times, and finally place it in a vacuum drying oven at 55 °C for 8 hours to obtain modified nano-silica; As Figure 1 shown, it is the particle size distribution diagram of this high-temperature resistant modified nano-silica plugging agent;
[0034] S2: Add 1.8 g of modified nano-silica and 110 ml of toluene into a reaction vessel, ultrasonically disperse for 10 minutes, add 1.44 g of acrylic acid and 1.07 g of o-toluidine, keep stirring rapidly until dissolved, introduce nitrogen for 20 minutes, heat the reaction system to 45 °C, stir and react for 14 hours, raise the temperature to 80 °C, and continue to react for 2 hours. After the reaction is completed, wash and dry the prepared sample to obtain a high-temperature-resistant modified nano-silica plugging agent.
[0035] Example 2
[0036] This example provides a preparation method of a modified nano-silica plugging agent, and the specific steps are as follows:
[0037] S1: Place nano-silica with a sheet diameter of 20 nm in a vacuum drying oven at 80 °C and dry for 12 hours. Accurately weigh 3 g of the dried nano-silica, add it to a 50 ml ethanol / water dispersion liquid, ultrasonically disperse for 50 minutes, then dropwise add 3 g of γ-methacryloxypropyltrimethoxysilane while stirring, react at a temperature of 80 °C for 10 hours, wash with ethanol for 5 times repeatedly, and finally place it in a vacuum drying oven at 60 °C and dry for 10 hours to obtain modified nano-silica; as Figure 2 shown, it is the particle size distribution diagram of this high-temperature-resistant modified nano-silica plugging agent;
[0038] S2: Add 3 g of modified nano-silica and 120 ml of toluene into a reaction vessel, ultrasonically disperse for 15 minutes, add 2.16 g of acrylic acid and 2.14 g of N-methylaniline, keep stirring rapidly until dissolved, introduce nitrogen for 30 minutes, heat the reaction system to 50 °C, stir and react for 16 hours, raise the temperature to 90 °C, and continue to react for 3 hours. After the reaction is completed, wash and dry the prepared sample to obtain a high-temperature-resistant modified nano-silica plugging agent.
[0039] Example 3
[0040] This example provides a preparation method of a modified nano-silica plugging agent, and the specific steps are as follows:
[0041] S1: Place nano-silica with a sheet diameter of 15 nm in a vacuum drying oven at 70 °C and dry for 10 hours. Accurately weigh 2 g of the dried nano-silica, add it to a 40 ml ethanol / water dispersion liquid, ultrasonically disperse for 40 minutes, then dropwise add 2 g of γ-methacryloxypropyltrimethoxysilane while stirring, react at a temperature of 70 °C for 8 hours, wash with ethanol, wash repeatedly for 3 times, and finally place it in a vacuum drying oven at 55 °C and dry for 8 hours to obtain modified nano-silica;
[0042] S2: Add 2.5 g of modified nano-silica and 110 ml of toluene into a reaction vessel, ultrasonically disperse for 10 minutes, add 1.8 g of acrylic acid and 1.5 g of N-methylaniline, keep stirring rapidly until dissolved, introduce nitrogen for 20 minutes, heat the reaction system to 48 °C, stir and react for 14 hours, raise the temperature to 85 °C, and continue to react for 2 hours. After the reaction is completed, wash and dry the prepared sample to obtain a high-temperature-resistant modified nano-silica plugging agent.
[0043] To further illustrate the effects of the modified nano-silica plugging agent and the water-based drilling fluid in the present invention, performance tests were carried out on the modified nano-silica plugging agent and the water-based drilling fluid prepared by the methods of Example 1, Example 2 and Example 3.
[0044] 1. Particle size test of the modified nano-silica plugging agent
[0045] The particle size of the novel high-temperature-resistant modified nano-silica plugging agent was tested using a BI-200SM laser scattering instrument produced by Brookhaven Instruments Corporation, USA. The particle size test results of the novel high-temperature-resistant modified nano-silica plugging agent prepared in Example 1 and Example 2 are respectively as Figure 1 、 Figure 2 shown. The particle size of the novel high-temperature-resistant modified nano-silica plugging agent of the present invention is distributed between 35 - 250 nm, and the average particle size is 60 nm, indicating that the synthesized polymer plugging agent is of nano size and has a wide distribution range, which can effectively plug nano-cracks of different nano-sizes.
[0046] 2. Rheological properties and fluid loss and wall-building properties test of the drilling fluid
[0047] The application method of the novel high-temperature-resistant modified nano-silica plugging agent of the present invention is mainly illustrated by the following specific formula. Based on 100 parts by weight of fresh water, the water-based drilling fluid formula is illustrated by the following method in this example. The specific water-based drilling fluid formula is as follows: 100 parts by weight of water + 3 parts by weight of bentonite + 0.2 part by weight of sodium hydroxide + 0.02 part by weight of potassium polyacrylamide coating agent (KPAM) + 0.4 part by weight of polyanionic cellulose (PAC-LV) + 5 parts by weight of humic acid propanesulfonamide copolymer (RSTF) + 5 parts by weight of sulfonated phenolic resin fluid loss reducer (SMP-1) + 5 parts by weight of amidoamine anti-collapse agent (FRH) + 1 part by weight of anti-sticking fluid loss reducer (PPL) + 4 parts by weight of anti-sticking lubricant (FK-10) + 0.4 part by weight of emulsifier (SP-80) + 1.2 parts by weight of desulfurizer + 0.4 part by weight of calcium oxide alkalinity regulator + 10 parts by weight of nano-barite.
[0048] The specific preparation process of the water-based drilling fluid is as follows:
[0049] (1) Pre-hydrated bentonite slurry
[0050] Add 3 parts by weight of bentonite to 100 parts by weight of tap water at a temperature of 70 °C. After stirring evenly at room temperature, add 0.2 parts by weight of sodium hydroxide. After fully stirring for 30 minutes, seal and let it stand for hydration for 24 hours.
[0051] (2) Preparation of drilling fluid
[0052] Take 4 parts of 400 ml of pre-hydrated bentonite slurry respectively, and then add 0.02 parts by weight of polyacrylamide potassium salt coating agent (KPAM), 0.4 parts by weight of polyanionic cellulose (PAC-LV), 5 parts by weight of humic acid propanesulfonamide copolymer (RSTF), 5 parts by weight of sulfonated phenolic resin filtration reducer (SMP-1), 5 parts by weight of amidoamine anti-collapse agent (FRH), 1 part by weight of anti-sticking and filtration-reducing agent (PPL), 4 parts by weight of anti-sticking lubricant (FK-10), 0.4 parts by weight of emulsifier (SP-80), 1.2 parts by weight of desulfurizer, 0.4 parts by weight of calcium oxide alkalinity regulator, and 10 parts by weight of nano-barite in sequence. Each time a substance is added, it needs to be stirred for 10 - 15 minutes.
[0053] After stirring evenly, add 0, 4 g, 8 g, 12 g, and 16 g of the high-temperature resistant modified nano-silica plugging agent prepared in Example 1 above to the 4 parts of bentonite slurry respectively to prepare five kinds of drilling fluids with different addition amounts of high-temperature resistant modified nano-silica plugging agent, named drilling fluid 1, drilling fluid 2, drilling fluid 3, drilling fluid 4, and drilling fluid 5 respectively, where drilling fluid 1 does not contain high-temperature resistant modified nano-silica plugging agent and serves as a blank experimental group.
[0054] According to the national standard of the People's Republic of China GB / T 16783.1 - 2014 "Petroleum and natural gas industries - Drilling fluids - Field testing - Part 1: Water-based drilling fluids", test the rheology and fluid loss and wall building properties of the prepared drilling fluids before and after aging respectively, and record the results in Table 1.
[0055] Table 1 Record table of rheological properties and filtration properties of drilling fluids
[0056]
[0057] Note: AV - Apparent viscosity, unit: mPa·s; PV - Plastic viscosity, unit: mPa·s; YP - Yield point, unit: Pa; API - Filtration loss at normal temperature and medium pressure, unit: mL; HTHP - Filtration loss at high temperature and high pressure, unit: mL.
[0058] As can be seen from the results shown in Table 1, compared with the drilling fluid without the high-temperature resistant modified nano-silica plugging agent prepared in Example 1, when the dosage of the high-temperature resistant modified nano-silica in the drilling fluid is 4 to 16 parts by weight, the performance of the drilling fluid is not significantly affected, indicating that the drilling fluid plugging agent has good compatibility. With the increase in the dosage of the high-temperature resistant modified nano-silica plugging agent, under the same experimental conditions, the apparent viscosity and plastic viscosity of the drilling fluid gradually increase, and the influence on shear force is relatively small. For the drilling fluid aged at 150 °C for 16 hours, with the increase in the dosage of the high-temperature resistant modified nano-silica plugging agent, the high-temperature high-pressure filtration loss gradually decreases, and when the dosage is 12 parts by weight, the high-temperature high-pressure filtration loss is the smallest, indicating that the high-temperature resistant modified nano-silica plugging agent has good rheological properties and water-loss wall-building properties, and can effectively reduce the high-temperature high-pressure filtration loss of the drilling fluid. Even in a high-temperature environment, it can provide good plugging performance, effectively prevent the filtrate from entering the formation, and improve the wellbore stability.
[0059] 3. Drilling Fluid Plugging Performance Test
[0060] An artificial core was used to simulate the nano-fractured formation. By measuring the average flow rate of the drilling fluid system in the artificial core and using Darcy's formula, the permeability K of the artificial core before and after adding the high-temperature resistant modified nano-silica plugging agent was calculated as K = Qμl / (AΔP), and then the plugging rate of the new high-temperature resistant modified nano-silica plugging agent for the artificial core was calculated to evaluate its plugging performance. Table 2 shows the record table of the plugging effect of the new high-temperature resistant modified silica on the artificial core.
[0061] Table 2 Experimental Data Table for Evaluating the Plugging Performance of Artificial Cores
[0062]
[0063] Note: The core length is 5 cm and the diameter is 2.5 cm.
[0064] As can be seen from the results shown in Table 2, compared with the base slurry without the high-temperature resistant modified nano-silica plugging agent, after adding different proportions of the high-temperature resistant modified nano-silica plugging agent, the plugging rate of the core increased, and when 12 g of the high-temperature resistant modified nano-silica plugging agent was added, the plugging rate of the core reached 96.8% for all, indicating that the high-temperature resistant modified nano-silica plugging agent can effectively plug the nano-fractures and thus prevent the drilling fluid from entering the core.
[0065] The specific embodiments described above are only preferred embodiments of the present invention and do not impose any form of limitation on the present invention. Although the present invention has been disclosed above with preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to equivalent embodiments by using the technical content disclosed above within the scope of the technical solution of the present invention. However, as long as the content does not depart from the technical solution of the present invention, any simple modification, equivalent change, and modification made to the above embodiments based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A modified nano-silica plugging agent, characterized in that, It includes nano-silica, an amino-group-containing silane coupling agent, acrylic acid, and an aromatic amine substance.
2. The modified nano-silica plugging agent according to claim 1, wherein The amino-group-containing silane coupling agent includes γ-methacryloxypropyltrimethoxysilane or γ-aminopropyltriethoxysilane.
3. A modified nano-silica plugging agent according to claim 1, wherein, The aromatic amine substance includes o-toluidine or N-methylaniline.
4. A modified nano-silica plugging agent according to claim 1, characterized in that, The sheet diameter of the nano-silica is 10 nm to 20 nm.
5. A method for preparing the modified nano-silica plugging agent according to any one of claims 1 to 4, characterized in that, It includes the following steps: Modification of nano-silica: Add the dried nano-silica into a dispersion liquid for ultrasonic dispersion, dropwise add the amino-group-containing silane coupling agent while stirring, wash and dry after the reaction to obtain modified nano-silica. Add the modified nano-silica and toluene into a reaction vessel, add acrylic acid and the aromatic amine substance after ultrasonic dispersion, stir until dissolved, introduce nitrogen, heat up the reaction system, wash and dry after the reaction is completed to obtain the modified nano-silica plugging agent.
6. The preparation method of a modified nano-silica plugging agent according to claim 5, characterized in that, The molar ratio among the modified nano-silica, acrylic acid, and the aromatic amine substance is (0.05 - 0.05):(0.02 - 0.03):(0.01 - 0.02).
7. The preparation method of a modified nano-silica plugging agent according to claim 5, characterized in that, The heating method of the reaction system is: First heat up to 45°C - 50°C, stir and react for 14 h - 16 h, then raise the temperature to 80°C - 90°C and continue to react for 2 h - 3 h.
8. A water-based drilling fluid, characterized in that, It includes the modified nano-silica plugging agent according to any one of claims 1 - 4 or the modified nano-silica plugging agent prepared by the preparation method according to any one of claims 5 - 7.
9. A water-based drilling fluid according to claim 8, characterized in that, It further includes water, bentonite, sodium hydroxide, potassium polyacrylamide coating agent, polyanionic cellulose, humic acid propanesulfonamide copolymer, sulfonated phenolic resin filtration reducer, amidoamine anti-collapse agent, anti-sticking filtration reducer, anti-sticking lubricant, emulsifier, desulfurizer, calcium oxide alkalinity regulator, nano-barite weighting agent.
10. A water-based drilling fluid according to claim 9, wherein, By weight fraction, based on 100 parts of water, the addition amount of the bentonite is 2 - 4 parts, the addition amount of the sodium hydroxide is 0.1 - 0.3 parts, the addition amount of the potassium polyacrylamide coating agent is 0.01 - 0.03 parts, the addition amount of the polyanionic cellulose is 0.3 - 0.8 parts, the addition amount of the humic acid propanesulfonamide copolymer is 4 - 6 parts, the addition amount of the sulfonated phenolic resin filtration reducer is 5 - 6 parts, the addition amount of the amidoamine anti-collapse agent is 3 - 5 parts, the addition amount of the anti-sticking filtration reducer is 1 - 2 parts, the addition amount of the anti-sticking lubricant is 4 - 5 parts, the addition amount of the emulsifier is 0.3 - 0.5 parts, the addition amount of the modified nano-silica plugging agent is 1 - 5 parts, the addition amount of the desulfurizer is 1 - 1.5 parts, the addition amount of the calcium oxide alkalinity regulator is 0.3 - 0.5 parts, and the addition amount of the nano-barite weighting agent is 0 - 20 parts.
Citation Information
Cited By
High-temperature-resistant dispersing type emulsified asphalt anti-collapse agent for oilfield drilling and preparation method of high-temperature-resistant dispersing type emulsified asphalt anti-collapse agent
CN121046045A